1999
DOI: 10.3109/13550289909045378
|View full text |Cite
|
Sign up to set email alerts
|

Absence of evidence of Borna disease virus infection in Swedish patients with Chronic Fatigue Syndrome

Abstract: Chronic Fatigue Syndrome (CFS) is characterized by debilitating fatigue, somatic symptoms and cognitive impairment. An infectious basis has been proposed; candidate agents include enteroviruses, herpesviruses, retroviruses and Borna disease virus (BDV), a novel neurotropic virus associated with neuropsychiatric disorders. Sera and peripheral blood mononuclear cells (PBMC) from Swedish CFS patients were assayed for evidence of infection using ELISA and Western immunoblot for detection of antibodies to BDV prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 22 publications
0
29
0
3
Order By: Relevance
“…Other examples of inconsistent NAAT-based associations are atherosclerosis linked to Helicobacter pylori (22), herpes simplex virus, cytomegalovirus and Epstein-Barr virus (14,21), and periodontal microorganisms (6,10,11). A number of "syndromes of yet unknown etiology," including chronic fatigue syndrome, fibromyalgia, and sarcoidosis, have been also linked to Mycoplasma (9, 26), Borna disease virus (10, 31), HHV-8 (4, 7, 12), and Propionibacterium spp.…”
Section: Wanted: Etiologic Agentsmentioning
confidence: 99%
“…Other examples of inconsistent NAAT-based associations are atherosclerosis linked to Helicobacter pylori (22), herpes simplex virus, cytomegalovirus and Epstein-Barr virus (14,21), and periodontal microorganisms (6,10,11). A number of "syndromes of yet unknown etiology," including chronic fatigue syndrome, fibromyalgia, and sarcoidosis, have been also linked to Mycoplasma (9, 26), Borna disease virus (10, 31), HHV-8 (4, 7, 12), and Propionibacterium spp.…”
Section: Wanted: Etiologic Agentsmentioning
confidence: 99%
“…The differences in prevalence could be due to the use of different assay systems (immunofluorescence [IF] assay [4,5,37,38], Western blot [WB] analysis [8,14,15,21,23,24,40,47,50], enzyme-linked immunosorbent assay [14,20,24], and electrochemiluminescence immunoassay [ECLIA] [53]) with different sensitivities and specificities. Particularly, in most of the previous reports that examined BDV antibodies by WB analysis, the specificity for BDV has not been considered, giving rise to the possibility of false-positive results.…”
mentioning
confidence: 99%
“…Among these 9 studies, 2 studies did not find an association between BDV and CFS. Evengard et al reported that in Swedish patients, there was nonspecific immunoreactivity in ELISA to BDV in CFS sera (due to infectivity with other microbes or viral agents, as well as being bound to b-galactosidase), which was not confirmed by WB; in addition to RT-PCR detection of P-gene transcripts in PBMC (18). However, the geographic differences and other factors could be the reason for this discrepancy.…”
Section: Discussionmentioning
confidence: 94%
“…In a study by Bode et al the role of BDV in the etiology of CFS was no significant (17). Evengardand et al did not support the role of BDV in the pathogenesis of CFS (18). In a Japanese study by Nakaya et al the prevalence of BDV p24RNA and antibody in Peripheral Blood Mononuclear Cells (PBMCs) and serum of patients with CFS was 32%, supporting the association between BDV and CFS (19).…”
Section: Contextmentioning
confidence: 91%